Treatment of concomitant SLAP lesion in patients aged 45 and above who underwent arthroscopic rotator cuff repair: Tenotomy versus labral repair? (Annals of Medical Research, 2024)
Aim: The current study aimed to compare the clinical and functional outcomes of the long-head biceps tendon (LHBT) tenotomy or labrum repair for the biceps-labral complex in the presence of superior labrum anterior-posterior (SLAP) lesion accompanying Goutallier type 0-I-II rotator cuff injury in patients aged 45 and above who underwent arthroscopic repair.Materials and Methods: A retrospective analysis was conducted on 1,148 patients who underwent arthroscopic shoulder surgery. A total of 223 patients, who underwent arthroscopic repair for Goutallier type 0, I, and II rotator cuff tears (RCT) and received simultaneous treatment for SLAP lesions through either LHBT tenotomy or labral repair, were included in the study. Patients were divided into two groups according to the treatment of SLAP lesions such as tenotomy (n=78) and repair (n=145). Demographic data, pre-operative, post-operative 3-month, and 12-month range of motion, visual analog scale (VAS), and Constant Murley Scale (CMS) were compared.Results: Flexion and external rotation were significantly higher in the tenotomy group, and internal rotation in the repair group (p
Keywords: Rotator cuff injuries; SLAP tears; Shoulder injuries; Arthroscopic surgeries